REHSOS: Jurnal Ilmiah Rehabilitasi Sosial Vol. xx No. x, Juli, 2023: KETERAMPILAN SOSIAL PENYANDANG DISABILITAS SENSORIK NETRA DI SENTRA WYATA GUNA BANDUNG - Anindita Putri Susanti; Raden Enkeu Agiati; Suhendar Suhendar (Jurnal Ilmiah Rehabilitasi Sosial (Rehsos), 2023)
Social skills of persons with visual sensory disabilities are the ability to effective communicate, interact, cooperate, and motivation with the social environment. This research aims to obtain an empirical description of: 1) the characteristics of the respondents, 2) effective communicate skills, 3) interaction skills, 4) cooperation skills, and 5) motivation skills of the respondents. The method used in this research is a quantitative research method with a descriptive survey. The sources used are primary and secondary sources. The population in this research is 20 blind sensory disabilities in the Sentra Wyata Guna Bandung. The sampling technique in this research is a census. The data collection techniques used are: 1) questionnaire, 2) observation, and 3) documentation study. The research instrumen used a rating scale. The validity test used is the face validity test, the reliability test used Alpha Cronbach. The results of this research show that the ability of social skills persons with visual sensory disabilities are in the high category. However, the ability to cooperate on the social skills of persons with visual sensory disabilities has the lowest score. Therefore, it is proposed the program "Collaborative Training with Recreation Skill Group for People with Visual Sensory Disabilities” at the Sentra Wyata Guna Bandung. Keywords: Social Skills, Effective Communication Skills, Interaction Skills, Cooperation Skills, Motivation Skills, and Visual Sensory Disabilities